Comparison of direct and perturbation approaches to analysis of infinite-dimensional feedback control systems - Grabowski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
For general boundary control systems in factor form some necessary and sufficient conditions for generation of an analytic exponentially stable semigroup are proposed in both direct and perturbation forms for comparison. The direct approach is applicable to operators with the numerical range satisfying certain additional conditions. In particular, it applies to operators similar to convexoids and therefore it generalizes previous results known for hyponormal operators.
Keywords: perturbation; semigroups; systems in factor form; spectral operators